Karakteristik Kimia dan Sensori Stik Bawang dengan Substitusi Tepung Biji Labu Kuning (Cucurbita moscata) - Karina Aida Jefferson; Noli Novidahlia; Distya Riski Hapsari (Universitas Djuanda, 2025)
Garlic sticks are extruded snacks made from wheat flour. This study aims to obtain the selected formulation of onion stick products based on chemical characteristics (protein and crude fibre content) and onion stick sensory. This research design uses a completely randomised design (CRD) with 4 levels of treatment. The results showed that the ratio of flour and pumpkin seed flour had an effect on protein content, crude fibre content, colour quality, aroma quality, texture quality, taste quality of pumpkin seeds, on the level of liking for colour, aroma, taste, and overall but had no effect on taste quality (savoury) and level of liking for texture. The selected sticks were based on the treatment of 60% wheat flour and 40% pumpkin seed flour with a moisture content of 2.76%, ash content of 3.8%, fat content of 37.15%, acid insoluble ash content of 0.10%, carbohydrate content of 40.13%, protein content of 16.16% and crude fibre content of 2.99%. The sensory quality characteristics of the selected onion sticks are colour towards brownish yellow, aroma towards not languorous, taste towards savoury and towards pumpkin seed taste, and texture towards crunchy and towards not brittle. The hedonic value of the selected onion sticks has aroma, taste, texture and overall towards liking but colour towards disliking.